Meningkatkan Kemampuan Membaca Permulaan Melalui Media Kartu Suku Kata Bergambar pada Anak Disabilitas Intelektual Ringan - Putri, Enjeli Dwi; Iswari, Mega; Rahmahtrisilvia, Rahmahtrisilvia; Zulmiyetri, Zulmiyetri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by a problem found at SLB Negeri 1 Linggo Sari Baganti involving Grade III students with mild intellectual disabilities. The purpose of this research was to examine the improvement of beginning reading skills through the use of pictured syllable card media. The study employed a Single Subject Research (SSR) method with an A-B design. Phase (A) represented the initial condition before the intervention, while Phase (B) was the intervention phase where students received treatment using pictured syllable cards. The baseline phase (A) was conducted over three sessions. The intervention phase (B), using the pictured syllable card media, was conducted over nine sessions. The research results showed that in the baseline phase (A), the percentage scores were 12.5%, 12.5%, and 12.5%. In the intervention phase (B), the scores increased to 25%, 25%, 37.5%, 50%, 62.5%, 75%, and reached 100% in the final three sessions. Based on the findings, it can be concluded that the use of pictured syllable cards during the intervention phase was effective in improving beginning reading skills in students with mild intellectual disabilities